Vegetation Dynamics and its Effect on Soil Loss Under different Landuse Systems in Bhetagad Watershed, Indian Central Himalayas - B. K. Joshi (Journal of Soil and Water Conservation, 2022)
The Indian Himalayas are very prone to soil erosion due to steep slopes and faulty landuse system. Most of the watersheds of the region are dominated by forestland with maximum area under open pine forest (degraded forest). Animal grazing (heavy to very heavy) and human interventions have significantly reduced biomass availability and ground vegetative cover. Vegetation has long been recognized as an important means of controlling soil erosion (Morgan 1986). In the Himalayan region agriculture practices without any tree cover in steep upland farming systems makes the land highly susceptible to soil erosion which reduces soil fertility ( Rai & Sharma 1998, Basavaraj et al., 2000 and Sharma et al. 2000). Although a few Himalayan watersheds have well maintained agriculture terraces but the removal of vegetal cover through various activities, grazing lands and development of new tea plantation have caused increase in the rate of soil erosion. In view of this, a study was conducted to assess the effect of various land uses and practices on runoff and soil and nutrient losses in the Bhetagad watershed in the kumaon Himalayas.